Two novel fomannosane-type sesquiterpenoids from the culture of the basidiomycete Agrocybe salicacola - Liu, Liang-Yan (Springer Berlin Heidelberg, 2012)
Two novel fomannosane-type sesquiterpenoids, agrocybins H (1) and I (2), together with a known compound illudosin (3), were isolated from the culture broth of the mushroom Agrocybe salicacola. Their structures were elucidated by extensive spectroscopic analysis. The relative stereochemistry of 1 was determined by the use of single crystal X-ray crystallographic diffraction. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0031-2 and is accessible for authorized users.